Akurasi Pengkodean Injury dan External Causes Berdasarkan ICD-10 dan ICD-9 CM di Rumah Sakit X - Sukawan, Ari; Putra, Dony Setiawan Hendyca; Barsasella, Diana; Rahmawati, Fitria Dewi (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
Accurate disease diagnosis coding is essential as it affects morbidity reporting, errors in determining medical procedures, billing issues, and invalidity as legal evidence. One example is injury coding, where ICD-10 guidelines require the 4th and 5th digits to indicate the location and activity associated with the injury. A preliminary study at X Hospital revealed that 80% of medical records had inaccurate injury coding, and external cause codes were absent. The issue is suspected to stem from the lack of coder training on injury and external cause coding. This study aims to assess the accuracy of injury and external cause coding based on ICD-10 and ICD-9 CM. It uses a descriptive approach with a sample of 65 medical records out of a total population of 77 from the fourth quarter of 2023, selected using simple random sampling. Data were collected through observation by reviewing medical records and completing observation sheets, then analyzed univariately. The results showed 66.2% of injury codes were inaccurate, 100% of external cause codes were inaccurate, and 83.08% of procedure codes were accurate. Most inaccuracies were due to the omission of the fifth digit for fractures and the absence of external cause coding.